Momordica balsamina crude acetone leaf extract impedes the human HT-29 colon cancer cell invasiveness, migration and adhesion by inhibiting ros-mediated TNF-a/NF-kB/MMP-2/-9 signalling pathway - Serala, Karabo (My University, 2020)
Metastatic cancer remains incurable and accounts for 90% of cancer-related deaths (He et al., 2019). Therefore, there’s an urgent need to find anti-metastatic drugs with novel therapeutic targets (Zhang et al., 2018). Medicinal plants are promising sources of novel compounds with anti-metastatic activity (Tungsukruthai et al., 2018). This study investigated the anti-metastatic effects of Momordica balsamina L. crude acetone leaf extract in human HT-29 colon cancer cells. Powdered leaves of M. balsamina were macerated in acetone and reconstituted in dimethyl sulfoxide (>99.9%). The cytotoxic effect of the M. balsamina extract was investigated using the MTT assay. The acridine orange/ethidium bromide dual staining assay was used to show that the chosen concentrations of the M. balsamina extract do not induce apoptosis. The effect of the M. balsamina extract on reactive oxygen species formation and epithelial to mesenchymal transition-related morphological changes were assessed by the DCFH2-DA assay and light microscopy, respectively. The anti-invasive, anti-migratory and anti-adhesive effects of the M. balsamina extract were investigated using the cell invasion, wound-healing and cell adhesion assays, respectively. The adhesion of HT-29 cells to collagen I, II and IV, fibronectin, laminin, tenascin C and vitronectin was assessed using the ECM-cell adhesion array kit. Furthermore, western blotting was used to assess the effect of the M. balsamina extract on the expression of TNF-α, NF-κB, MMP-2, MMP-9 and TIMP-3. The findings revealed that the M. balsamina extract significantly inhibited the viability of HT-29 cells at concentrations above 50 µg/ml but had no effect on the viability of C3A liver cells at 40 and 80 µg/ml. Apoptotic features such as cell shrinkage, nuclei condensation, loss of membrane function and formation of apoptotic bodies were observed at 48 hours exposure to the M. balsamina extract. Reactive oxygen species formation, epithelial to mesenchymal transition, invasiveness, migration and adhesion were suppressed in HT-29 cells treated with the M. balsamina extract for 24 hours. The adhesion of HT-29 cells were varied amongst different extracellular matrix proteins. Furthermore, HT-29 cells treated with the M. balsamina extract showed a reduction in the expression of TNF-α, NF-κB, MMP-2 and MMP-9 proteins and an upregulation of TIMP-3 protein. In conclusion, the M. balsamina extract tested in this study impedes the metastatic cascade in HT-29 colon cancer cells by inhibiting the reactive oxygen species-mediated TNF-α/NF-κB/MMP-2/MMP-9 pathway. The findings suggest that M. balsamina L. may be a source of compounds with potential therapeutic use for the treatment of metastatic colon cancer.
Thesis (M.Sc.(Biochemistry)) -- University of Limpopo, 2020
Keywords: Anti-metastatics; Momordica balsamina; Cancer cells; Medicinal plant; Momordica; Metastasis